PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MOTOR HONDA DI ASTRA MOTOR PLAJU - Juairiah, Juairiah (Universitas Muhammadiyah Palembang, 2016)
Purpose - The purpose of this research was to determine the effect of the product quality to customer satisfiction Honda Motorcycle In Astra Plaju.Design/methodology - The design of this research was Associative and the data was used primary data. The Sample was including 100 respondents customer who use Honda Motorcycle In Astra Plaju. Findings – The results of F–test showed that there was influence of performance of product, capability of service on customer satisfaction Honda Motorcycle in Astra Plaju Palembang. The result of t test indicated that reliability variable partially most dominant effect on customer satisfaction.